The Potential and Limitations of Mobile Health and Insertable Cardiac Monitors in the Detection of Atrial Fibrillation in Cryptogenic Stroke Patients: Preliminary Results From the REMOTE Trial - Wouters, Femke; Gruwez, Henri; Vranken, Julie; Vanhaen, Dimitri; Daelman, Bo; Ernon, Ludovic; Mesotten, Dieter; Vandervoort, Pieter; Verhaert, David (Frontiers in Cardiovascular Medicine, 2022)
Aim: This study aims to explore the opportunities and hurdles of using implantable loop recorders (ILRs) and photoplethysmography-based mobile health (PPG-based mHealth) to detect atrial fibrillation (AF) in cryptogenic stroke and transient ischemic attack (TIA) patients. Methods and Results: Cryptogenic stroke or TIA patients (n = 39) received an ILR to search for AF and were asked to use a PPG-based mHealth application for six months simultaneously. They were randomized to smartphone or smartwatch monitoring. In total, 68,748 recordings were performed using PPG-based mHealth. Insufficient signal quality was more frequently observed in smartwatch (43.3%) compared to smartphone recordings (17.8%, p < .001). Simultaneously, continuous data was collected from the ILRs, resulting in approximately 6,660,000 minutes of data. The ILR algorithm detected 259 AF episodes in 10 patients; only 5 episodes in 1 patient were confirmed after physician revision; the other 254 episodes were labeled as sinus rhythm, ectopic beats, oversensing, or noise. The number of mHealth recordings decreased significantly over time in both smartphone and smartwatch groups (p < .001 and p = .002, respectively). Conclusion: PPG-based mHealth was able to detect AF in a patient in which AF was confirmed on the ILR. Nevertheless, both monitoring methods still require physician revision. Based on the preliminary observations, our paper illustrates the potential as well as the limitations of spot-check and semi-continuous rhythm monitoring using mHealth and continuous monitoring using ILRs to detect AF in cryptogenic stroke and TIA patients.